2007
DOI: 10.2193/2005-712
|View full text |Cite
|
Sign up to set email alerts
|

Hair Sampling Techniques for River Otters

Abstract: River otter (Lontra canadensis) populations have been difficult to monitor and information on densities is lacking throughout their range. To obtain DNA‐based population estimates of river otters we developed 2 traps to capture hair; a modified body‐snare and a modified foot‐hold trap. Of 82 traps activated 77 captured hairs (94%). Traps snagged 3–20 guard hairs per capture. Our capture rates of otter hair ranged from one capture per 3.6 trap nights to one capture per 156.6 trap‐nights. Our traps provide an ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…These survey dates represent the summer season for this region. We measured habitat characteristics at river otter latrines and un-used sites selected at random in conjunction with a study to develop noninvasive DNA sampling techniques for otters (DePue and Ben-David 2007). We located latrine sites by surveying both river banks with raft or kayak and on foot within 30 m from the water's edge, because previous studies demonstrated that most otter latrines occur within this distance (Bowyer et al 1995).…”
Section: Methodsmentioning
confidence: 99%
“…These survey dates represent the summer season for this region. We measured habitat characteristics at river otter latrines and un-used sites selected at random in conjunction with a study to develop noninvasive DNA sampling techniques for otters (DePue and Ben-David 2007). We located latrine sites by surveying both river banks with raft or kayak and on foot within 30 m from the water's edge, because previous studies demonstrated that most otter latrines occur within this distance (Bowyer et al 1995).…”
Section: Methodsmentioning
confidence: 99%
“…Hair snares are often used as a noninvasive way to survey for mesocarnivores, but results have been mixed. Depue and Ben-David [14] used hair snares to survey river otter (Lontra canadensis) population densities with great success, with over 90% of their snares detecting river otters. On the other hand, hair snares set to survey bobcat (Lynx rufus) and fisher (Pekania pennanti) populations in Vermont failed to detect a single animal, even though they were known to be in the area [8].…”
Section: Introductionmentioning
confidence: 99%
“…Hair collection enables genetic and stable isotope analysis to be undertaken. This trapping method could be very important in providing new information to assist goral conservation and management (Mowat and Strobeck , Darimont and Reimchen , Mowat and Paetkau , Depue and Ben‐David ). In our study, we also collected hairs of other species, such as roe deer ( Capreolus pygargus ) and wild boar ( Sus scrofa ).…”
Section: Discussionmentioning
confidence: 99%
“…Many noninvasive techniques for monitoring mammal populations have been developed and evaluated (Long et al ). One such method used for genetic or isotopic studies of endangered species is hair traps (Mowat and Strobeck , Mowat and Paetkau , Depue and Ben‐David ). However, most species for which this technique has been applied have been carnivores, even though the approach could be equally applicable to critically endangered and hard‐to‐catch herbivores (Largo et al , Sandfort ).…”
mentioning
confidence: 99%